Incidence of Symptomatic Venous Thromboembolism in Proximal Hamstring Repair: A Prospective Cohort Study. Issue 7 (15th July 2021) - Asokan, Ajay; Plastow, Ricci; Chang, Justin S.; Kayani, Babar; Moriarty, Peter; Thompson, Joshua W.; Haddad, Fares S.
Background: Surgical repair of proximal hamstring avulsion injuries can enable the return to preinjury levels of sporting function and minimize the risk of recurrence in both professional and recreational athletes. While venous thromboembolism (VTE) is a recognized complication of surgical repair, the incidence thereof is poorly reported in the literature. Purpose/Hypothesis: To report the incidence of symptomatic VTE after proximal hamstring avulsion repair and assess the efficacy of our thromboprophylaxis protocol. It was hypothesized that the incidence of VTE after proximal hamstring avulsion repair is low and that aspirin is an adequate choice of chemical prophylaxis. Study Design: Cohort study; Level of evidence, 2. Methods: We performed a prospective cohort study of 2 groups of patients who underwent proximal hamstring avulsion (partial and complete) repair between 2000 to 2020 with different thromboprophylaxis protocols. No patients were routinely screened for VTEs, and VTE was investigated only if clinically indicated. Prospectively collected data included demographics, the mechanism and sport that caused injury, use of bracing, and clinical diagnosis of deep vein thrombosis (DVT) or pulmonary embolism (PE). The first cohort (n = 380) was given mechanical prophylaxis in the form of compression stockings for 6 weeks postoperatively. The second cohort (n = 600) was given compression stockings and aspirin 150 mg once daily routinely, or prophylactic low–molecular weight heparin in high-risk individuals, until the 6-week follow-up. Patients in both cohorts underwent early mobilization after surgery; a hinged knee brace locked at 60° to 120° was provided if the tendon repair was under significant tension. The surgical technique and rehabilitation protocol remained consistent throughout the study. Results: The overall incidence of symptomatic VTE was 0.51%. A total of 5 patients developed symptomatic VTEs (3 DVTs, 2 PEs) in the first cohort, and no patients developed symptomatic VTEs in the second cohort (1.32% vs 0%; P = .0048). Conclusion: The incidence of symptomatic VTE after proximal hamstring avulsion repairs was extremely low. A combination of aspirin, early mobilization despite bracing, compression stockings, and good hydration was an effective thromboprophylaxis strategy.